The Effect Of Awards, Payroll, And Performance Allowances In Internal Control (Case Study: South Sumatra Provincial Government) - Henky Putrawan (Jurnal Indonesia Sosial Teknologi, 2023)
Human resource development in government organizations is a vital thing to be managed wisely and wisely, in line with the increasing expectations and demands of the community for the quality of public services. The purpose of this study is to analyze the effect of awards, payroll, and performance allowances in internal control in the organization of the Sumatra Province government Selatan. This research uses the Quantitative Research method. The source of data used in this study was using primary data obtained from questionnaires distributed to the State Civil Apparatus (ASN) located at the Economic Bureau of South Sumatera Province. Data analysis techniques in this study are multiple regression linear analysis, Correlation Coefficient (r), Determination Coefficient Analysis (R Square = R^2), and hypothesis test. The results showed that the variables of performance, salary, and performance allowances affected internal control by 82.3% while the remaining 8.7% was caused by variables other than independent variables in this study.